Difference in apical resorption activity during rat molar root formation in response to mechanical force. (27th February 2023) - Lou, Yixin; Matsumoto, Yoshiro; Iseki, Sachiko; Ono, Takashi
Summary: Objective: To investigate whether there is a difference in apical resorption activity during the development of roots in response to mechanical force in vivo . Methods: Maxillary first molars (M1) from postnatal day (PN) 21 and PN35 male rats were selected as representatives of the root-developing and root-completing groups, respectively. A mechanical force of 3 cN was applied to M1 on PN21 and PN35, and the maxilla was collected on PN28 and PN42. Odontoclastogenesis and root morphology were investigated using micro-focus X-ray computed tomography, followed by immunohistochemistry and quantitative real-time polymerase chain reaction to clarify root resorption activity. Results: Development of the mesiobuccal root (MBR) preceded the mesial root (MR). In the PN28 force application (FA) group, the dentine was bent, but the histology, including Hertwig's epithelial root sheath (HERS), was intact. No odontoclasts and resorption lacunae were found in the apical area of the MRs, and only lateral root resorption was observed. External apical root resorption (EARR) was observed in the MR of PN42 (FA) and in the MBR of both PN28 (FA) and PN42 (FA). The expression of osteopontin changed accordingly. No significant change occurred in osteoprotegerin or receptor activator of nuclear factor-κB ligand expression in the MRs of the PN28 (FA) group. Limitations: Our animal model did not adequately simulate the clinical process of tooth movement in humans. Conclusions: Force application delayed HERS dissociation on the compression side of the developing roots, leading to inhibitory effects on cementogenesis, which resulted in decreased odontoclast differentiation and prevention of EARR.